Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1128/ec.4.9.1595-1598.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the TOR Pathway in Aspergillus nidulans

Abstract: We identified five genes encoding components of the TOR signaling pathway within Aspergillus nidulans. Unlike the situation in Saccharomyces cerevisiae, there is only a single Tor kinase, as in plant and animal systems, and mutant phenotypes suggest that the TOR pathway plays only a minor role in regulating nitrogen metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 28 publications
(30 reference statements)
3
40
0
2
Order By: Relevance
“…In S. cerevisiae and A. nidulans, mutations in downstream components of the TOR pathway confer increased resistance to rapamycin (Beck and Hall, 1999;Jacinto et al, 2001;Fitzgibbon et al, 2005). We found that the DmeaB and DareA mutants, but not the complemented strains, were slightly more resistant to rapamycin than the wild type ( Figure 3B).…”
Section: Nitrogen Repression Of Invasive Growth Requires Gln Synthetamentioning
confidence: 58%
See 2 more Smart Citations
“…In S. cerevisiae and A. nidulans, mutations in downstream components of the TOR pathway confer increased resistance to rapamycin (Beck and Hall, 1999;Jacinto et al, 2001;Fitzgibbon et al, 2005). We found that the DmeaB and DareA mutants, but not the complemented strains, were slightly more resistant to rapamycin than the wild type ( Figure 3B).…”
Section: Nitrogen Repression Of Invasive Growth Requires Gln Synthetamentioning
confidence: 58%
“…While TOR is a key player in nitrogen catabolite repression of S. cerevisiae (Beck and Hall, 1999;, its role in filamentous fungi remains controversial. TOR was suggested to have only a minor function in nitrogen metabolism of A. nidulans since mutations in TOR pathway genes did not have significant effects on the nitrogen utilization phenotype (Fitzgibbon et al, 2005). The discrepancy could partly be explained by the fact that several components of the TOR and nitrogen regulatory pathways, such as Ure2, MeaB, or Nmr1, are not conserved between S. cerevisiae and filamentous fungi.…”
Section: Role Of Tor and Meab In Nitrogen Repressionmentioning
confidence: 88%
See 1 more Smart Citation
“…Namely, Cpp1 shares significant similarity with PPE-1 protein, which is a probable cell-shape-control PP2Ac in N. crassa (E value, 0.0) (unpublished; GenBank accession no. XM_951629), and with SitA, which is a PP2Ac involved in the TOR pathway of Aspergillus nidulans (E value, 8e-165) (Fitzgibbon et al, 2005; GenBank accession no. CAG30555).…”
Section: Resultsmentioning
confidence: 99%
“…The genes AN5174 and AN7428 are orthologues of atg5 and atg7, respectively, and both are involved in the formation of autophagosomes in S. cerevisiae (Pollack et al, 2009). TipA is the orthologue of baker's yeast Tip41 (Fitzgibbon et al, 2005), which induces autophagy by inhibiting TOR signalling. Induction of Atg7 and Atg26 together with other autophagy-related genes was also observed in carbon-starved A. niger cultures (Nitsche et al, 2012).…”
Section: Programmed Cell Death During Carbon Starvationmentioning
confidence: 99%